SOSIALISAI STRATEGI PEMASARAN UNTUK MENYIAPKAN JIWA KEWIRAUSAHAAN BAGI SISWA-SISWI DI SEKOLAH MIFTAHUL ULUM KABUPATEN SERANG - Fuadi, Fuadi; Susanto, Denies; Jahro, Asri Nabila (Gapenas Publisher, 2025)
This community service aims to socialize effective marketing strategies in preparing an entrepreneurial spirit for students at MA Miftahul Ulum School, Serang Regency. In the context of rapid economic development, entrepreneurship is a very important skill for the younger generation to have. Socialization activities are carried out through a series of interactive trainings that include basic entrepreneurial theories, digital marketing techniques, branding, and market analysis. The methods used include lectures, group discussions, and practical simulations that allow students to directly design marketing plans for the products they develop. Active participation of students in this activity is expected to improve their understanding and skills in implementing marketing strategies. The results of the socialization activities showed a significant increase in students' understanding of the concept of entrepreneurship and their ability to design innovative marketing strategies. Feedback from students showed high enthusiasm and interest in the material presented. It is hoped that this program will not only improve students' entrepreneurial spirit, but also make a positive contribution to the development of the local economy in Serang Regency through innovation and business that they can create in the future.